Anaerobic Roll Tube Media for Nonselective Enumeration and Isolation of Bacteria in Human Feces - Eller, Charles (1971)
Medium 10 (M10), developed for rumen bacteria and containing small amounts of sugars, starch, volatile fatty acids, hemin, Trypticase, yeast extract, cysteine, and sulfide, plus agar, minerals and CO(2)-HCO(3)-buffer, was used with the Hungate anaerobic method as a basal medium to evaluate the efficacy of various ingredients. Three-day-old colony counts from adults on normal diets (17 samples) were 0.55 × 10(11) to 1.7 × 10(11) per g (mean, 1.15 × 10(11)) for M10. Single deletion of volatile fatty acids, Trypticase, yeast extract, or sulfide did not reduce counts. Deletion of hemin or both Trypticase and yeast extract significantly lowered counts. Addition of fecal extract, rumen fluid, 1% dehydrated Brain Heart Infusion (BHI) or 2 to 6% liver infusion did not increase counts; 1% dehydrated bile or 3.7% BHI markedly depressed them. Decreasing the gas-phase CO(2) concentration from 100 to 5% with N(2) and correspondingly lowering the HCO(3) had little effect. Counts in supplemented Brewer Thioglycollate (Difco), BHI, and Trypticase soy agar were similar or lower than in M10; ease in counting was best in M10. Comparison of features of 88 predominant strains of fecal bacteria randomly isolated indicated that M10 supported growth of as many or more species of bacteria as compared to supplemented BHI. The results suggest that predominant bacteria of human feces, in general, are not as nutritionally fastidious as rumen bacteria and indicate that media for counts or isolation containing large amounts of rich organic materials are neither necessary nor desirable when adequate anaerobic techniques are used.